Dawn of Justice: Evaluating the Alignment of Women and Children in Aceh's Qanun Jinayat - Muzakkir Muzakkir (Al-Ahkam, 2022)
Aceh Qanun No. 6 of 2014 concerning the Jinayat Law can potentially eliminate justice for women and children. Through a literature study using a descriptive-analytical method, this article aims to interpret the substance of the Qanun Jinayat. The results show that the Qanun Jinayat has not taken sides with women and children. The first evidence, the preliminary evidence requirement for rape victims in the Qanun Jinayat, provides an opportunity to harm women. Victims may be unable to show evidence due to their psychological pressure. The second piece of evidence, the existence of legal dualism, between Article 81 and Article 82 of the Child Protection Law and Article 47 of the Qanun Jinayat, provides opportunities for violence to children. Qanun Jinayat provides lighter sentences to perpetrators. This article finds that the Qanun Jinayat was formulated and ratified with minimal involvement of many parties and absorption of community aspirations. The article recommends that the formulation of the Qanun Jinayat should be revised with consideration of the public benefit by involving modernist academics with a comprehensive religious education background.